The Urgency of Land Registration for Land Assets of Malang City Government - Paramita, Pinastika Prajna; Ayu, Isdiyana Kusuma; Anggraeny, Isdian (Universitas Internasional Batam, 2024)
Land in Malang City which is a land asset of the Malang City Government has not been registered which has resulted in some land being controlled by other parties without the knowledge of the Malang City Government. knowing the urgency of land certificate ownership of Malang City land assets and will not lose regional assets which when used by Third Parties will be a source of Regional Original Revenue. The problem to be researched is what are the legal consequences. The type of research used in this study is empirical juridical research with a sociological juridical approach. The Malang City Government is important to register its land as a city land asset, either with the right of use or the right of management. Land certificates that are already owned by the Malang City Government are able to provide legal certainty and legal protection to the Government and can increase the Regional Original Revenue of Malang City.